PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP MINAT DAN HASIL BELAJAR AL-QUR’AN HADIST SISWA KELAS VIII MTSN 6 KOTA PADANG - indrian saputra (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
This research was motivated by the fact that the class VIII Al-Qur'an Hadith teacher at MTsN 6 Padang City only used the lecture method in teaching. The research population was all class VIII students at MTsN 6 Padang City, totaling 350 students, with a sample of 187 students selected using the Slovin formula. Data was collected through questionnaires for the variables of teacher professional competence and interest in learning, while learning outcomes were obtained from documentation of MID scores. while the remaining 20.1% was influenced by other factors that were not researched. (3) The influence test also shows a t count of 5.451 with a significance of 0.004, which means a significance of <0.05, which means there is a significant influence between teacher professional competence (X) on learning outcomes (Y2). (4) From the R Square test, the value obtained is 0.851, which shows that teacher professional competence (X) has an influence of 85.1% on learning outcomes (Y2), while the remaining 14.9% is influenced by other factors not examined. in this research.